The Impact of Oil Price Volatility on the Economic Growth in Iran: An Application of a Threshold Regression Model - Tehranchian, Amir Mansour; Seyyedkolaee, Mohammad Abdi (International Journal of Energy Economics and Policy, 2017)
Oil price volatility is one of the main reasons for the economic crisis in the world. Therefore, investigate the relationship between volatility in oil prices and economic growth in an oilexporting country has special significance. In the present paper, the impact of oil price volatility on the economic growth in Iran has been tested by using the Threshold Regression (TR) model on time series data 1980-2014 extracted from the Central Bank of Iran (CBI). Findings of this study show that the oil price volatility equal to 1147.77 acts as a threshold value. Also, due to the fact that the coefficient of oil price volatility has decreased in the second regime compared to the first one, the effectiveness amount of the oil price volatility on economic growth has decreased over time. Keywords: Oil Price Volatility, Economic Growth, Threshold Regression Method, Economy of Iran. JEL Classifications: C51; E20; O40.